Cover Image. (1st April 2021) - Chen, Qiuman; Zheng, Liwen; Zhang, Yuxin; Huang, Xia; Wang, Feilong; Li, Shuang; Yang, Zhuohui; Liang, Fang; Hu, Jing; Jiang, Yucan; Li, Yeming; Zhou, Pengfei; et al.
Abstract : The cover image is based on the Original Article Special AT‐rich sequence‐binding protein 2 (Satb2) synergizes with Bmp9 and is essential for osteo/odontogenic differentiation of mouse incisor mesenchymal stem cells by Qiuman Chen et al., https://doi.org/10.1111/cpr.13016 .